Experimental investigation of the time- and rate-dependent behaviour of unsaturated clays - Bagheri, Meghdad (2018)
With the aim to achieve a better understanding of the time- and rate-dependent behaviour of unsaturated clays, particularly stiff natural clays, a critical review of the literature and a program of laboratory testing were carried out as part of this research. With emphasis on examining the effect of suction on viscous response, mainly primary and secondary consolidation (creep), stress-relaxation, and rate-dependency, a series of conventional multi-stage loading (MSL) oedometer tests, long-term single-stage loading (SSL) oedometer tests, and advanced constant-rate-of-strain (CRS) oedometer tests were carried out on natural and corresponding reconstituted specimens of a stiff clay namely, London Clay, retrieved from a site in the Isle of Sheppey, UK. The results obtained provide a significant contribution to the existing database and address important knowledge gaps highlighted from the literature review. The experimental studies performed included; a) An investigation of the effect of water reservoir surface roughness on the cavitation mechanism and performance of a newly designed high-capacity tensiometer (HCT), with regard maximum sustainable suction (smax) and maximum duration of measurements (tmax). b) An examination of the influence of soil suction on the primary and secondary consolidation of natural and reconstituted London Clay from a set of MSL and SSL oedometer tests. c) Characterisation of the stress-relaxation behaviour of the reconstituted London Clay subjected to suction and strain-rate variations from a set of CRS oedometer tests in an in-house designed suction-monitored cell. d) An examination of the coupled effects of suction and strain-rate on one-dimensional (1D) stress–strain response of reconstituted London Clay. Based on the experimental findings, the validity of the empirical relationships proposed in the literature for correlating time- and rate-dependency coefficients was examined and necessary modifications were proposed. The main experimental findings can be outlined as: - The mechanism of cavitation in tensiometers is indeed influenced by the surface roughness of the water reservoir. The new approach for expanding the range and duration of suction measurements for a newly designed HCT, based on hydrophilic coating of the reservoir walls, sounds promising. - The compression index (Cc) and creep index (Cαe) and the ratio α = Cαe/Cc for Sheppey London Clay are stress- and suction-dependent. The hypothesis of constant α for natural clays, as suggested by Mesri et al. (1994), is therefore rejected. - The volumetric creep deformations of unsaturated stiff clays appear to be relatively simply modelled by a creep law based on a power function. - A coupled effect of suction and strain-rate on 1D compression response was identified. At a constant suction, the higher the strain-rate, the higher the apparent preconsolidation pressure (σ′p). Similarly, at a constant strain-rate, the higher the suction, the higher the σ′p. - The values of relaxation coefficient (Rα) differ in saturated and unsaturated states. However, a clear relationship between Rα and suction was not found. The Rα = Cαe/Cc relationship, suggested by Yin et al. (2014) for saturated soft clays, appears, with an approximation, to be valid for the unsaturated stiff London Clay in the range of applied vertical stresses and soil suctions in this study. - The process of stress-relaxation in unsaturated clays is highly influenced by factors such as soil suction, pre-relaxation strain, stress, and strain-rate.